A Revealing New Addition to the Corpus of Alexander Decadrachms from Babylon - Taylor, Lloyd W. H.; Andric, Marko (KOINON: The International Journal of Classical Numismatic Studies, 2023)
A previously unknown example of the initial striking of the Babylon decadrachms of Alexander the Great brings to the corpus of the coinage a formerly unknown mint control, transitional between the controls observed on the Babylon Groups 1 and 2 tetradrachms. It corroborates the sequence of striking inferred from the progression of reverse iconographic details, and supports the inferred date of the decadrachm mintage commencing in 325 BC. Additionally, the greater confidence in obverse die identification offered by this coin indicates that the coinage was most probably struck from four rather than five obverse dies.